Religion and new immigrants' labor market entry in Western Europe - Koenig, Matthias; Maliepaard, Mieke; Guveli, Ayse (Ethnicities, 2016)
This paper analyzes the effects of religious participation upon a major socio-economic integration outcome, namely employment, among recent Christian and Muslim newcomers in three Western European destination countries: Germany, the Netherlands, and Great Britain. The paper revisits theoretical arguments about religious participation as an ethnic investment strategy or, alternatively, as a bridge to the societal mainstream. Drawing on the longitudinal dataset produced in the international survey project on ‘Socio-cultural Integration Processes among New Immigrants in Europe’ (SCIP), the paper puts these arguments to a rigorous test by analyzing effects of involvement in religious communities on employment and by scrutinizing channeling effects of the ethnic composition of religious congregations for recent migrants’ entry into mainstream versus ethnic niche economies. The paper finds only limited support for either of the two arguments, suggesting that religious participation is structurally decoupled from socio-economic integration. However, persisting net employment gaps between recent Christian and Muslim immigrants might indicate the existence of religiously marked and socio-economically consequential boundaries in Western Europe.
Gesehen am 29.04.2021